Hadith #2124 - Sunan Abi Dawud - Abdah bin Sulaiman al-Klabi عبدة بن سليمان الكلابي أبو محمد الكوفي; Ayoub al-Sakhtiyani أيوب السختياني; ibn Abbas; Ikrama عكرمة; Sa'id bin Abi Sa'id (Sunan Abi Dawud)
When a man who has a wife married a virgin he should stay with her seven nights ; if he marries to a woman who has been previously married he should stay with her three nights. (The narrator said:) If I say that he (Anas) narrated this tradition from the Prophet (ﷺ) I shall be true. But he said: The Sunnah is so-and-so.
Grade: Sahih

Hadith #2133 - Sunan Abi Dawud - Abdullah bin Yazid bin Zayd; Abu Qalaba, 'Abdullah bin Zayd al-Jarmi عبد الله بن زيد بن عمرو; Aisha bint Abi Bakr; Ayoub al-Sakhtiyani أيوب السختياني; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي (Sunan Abi Dawud)
The Prophet (ﷺ) said: When a man has two wives and he is inclined to one of them, he will come on the Day of resurrection with a side hanging down.
Grade: Sahih

Hadith #2182 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; Ayoub al-Sakhtiyani أيوب السختياني; Ibn Sirin محمد بن سيرين الأنصاري; Ma'mar bin Rashid معمر بن راشد; Yonus bin Jubayr al-Bahli, Abu Ghalab يونس بن جبير الباهلي أبو غلاب (Sunan Abi Dawud)
‘Abd Allah (bin Umar) said that he divorced his wife while she was menstruating. ‘Umar mentioned the matter to the Messenger of Allah(ﷺ). The Messenger of Allah(ﷺ) became angry and said “Command him, he must take her back and keep her back till she is purified, then has another menstrual period and is purified. Then if he desires he may divorce her during the period of purity before he has intercourse with her. This is the divorce for waiting period as commanded by Allaah, the Exalted.
Grade: Sahih

Hadith #2196 - Sunan Abi Dawud - Abdullah bin Kathir al-Dari عبد الله بن كثير الداري; Ayoub al-Sakhtiyani أيوب السختياني; Hameed bin Musa'da bin al-Mubarak حميد بن مسعدة بن المبارك; Mujahid bin Jabir مجاهد بن جبر (Sunan Abi Dawud)
Abd Yazid, the father of Rukanah and his brothers, divorced Umm Rukanah and married a woman of the tribe of Muzaynah. She went to the Prophet (ﷺ) and said: He is of no use to me except that he is as useful to me as a hair; and she took a hair from her head. So separate me from him. The Prophet (ﷺ) became furious. He called on Rukanah and his brothers. He then said to those who were sitting beside him. Do you see so-and-so who resembles Abdu Yazid in respect of so-and-so; and so-and-so who re
Grade: Hasan

Hadith #2198 - Sunan Abi Dawud - Ayoub al-Sakhtiyani أيوب السختياني; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Muhammad bin al-Fadl 'Aram محمد بن الفضل السدوسي أبو النعمان عارم; Tawus bin Kaysan طاوس (Sunan Abi Dawud)
Abu Dawud said “The opinion of Ibn ‘Abbas has been mentioned in the following tradition. “Ahmad bin Salih and Muhammad bin Yahya narrated this is the version of Ahmad (bin Salih)” from ‘Abd Ar Razzaq from Ma’mar from Al Zuhri from Abu Salamah din Abd Al Rahman bin ‘Awf and Muhammad bin ‘Abd Al Rahman bin Thawban from Muhammad bin Iyas that Ibn ‘Abbas, Abu Hurairah and ‘Abd Alah bin ‘Amr bin Al ‘As were asked about a virgin who is divorced three times by her husband. They
Grade: Sahih

Hadith #2225 - Sunan Abi Dawud - Abu Qalaba, 'Abdullah bin Zayd al-Jarmi عبد الله بن زيد بن عمرو; Ayoub al-Sakhtiyani أيوب السختياني; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Sulaiman bin Harb سليمان بن حرب; Thawban bin Bujdud (Sunan Abi Dawud)
Abu Dawud said “I heard Muhammad bin Isa narrating this tradition who said Mu’tamar narrated it to us. And he (Mu’tamar) said “ I heard Al Hakam bin Aban narrating this tradition. He did not mention the name of Ibn ‘Abbas. Abu Dawud said “Al Hussain bin Huraith wrote to me saying “Al Fadl bin Musa narrated from Ibn ‘Abbas to the same effect from the Prophet(ﷺ).
Grade: Sahih

Hadith #2257 - Sunan Abi Dawud - Ahmad bin Hanbal أحمد بن حنبل; Ayoub al-Sakhtiyani أيوب السختياني; Sa'id bin Jubayr سعيد بن جبير الأسدي (Sunan Abi Dawud)
Ibn ‘Umar said “The Apostle of Allaah(ﷺ) said to the spouses who invoked curses on each other. Your reckoning is in Allaah’s hands for one of you is liar there is no way for you to (remarry) her. He then asked Apostle of Allaah(ﷺ) what about my property? He replied “There is no property for you. If you have spoken the truth, it is the price for your having had the right to intercourse with her and if you have lied against her it is still more remote for you.
Grade: Sahih

Hadith #2319 - Sunan Abi Dawud - Ayoub al-Sakhtiyani أيوب السختياني; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; ibn Umar; Nafie' نافع مولى ابن عمر; Sulaiman bin Da'ud bin Da'ud سليمان بن داود بن داود بن علي (Sunan Abi Dawud)
The Prophet (ﷺ) said: The month consists of twenty-nine days, but do not fast till you sight it (the moon) and do not break your fast till you sight it. If the weather is cloudy, calculate it thirty days. When the twenty-ninth of Sha’ban came, Ibn Umar would send someone (who tried) to sight the moon for him. If it was sighted, then well and good; in case it was not sighted, and there was no cloud and dust before him (on the horizon), he would not keep fast the next day. If there appeared (o
Grade: Sahih

Hadith #2320 - Sunan Abi Dawud - Abdul Wahab bin 'Abdul Majeed al-Thaqaf عبد الوهاب بن عبد المجيد الثقفي; Ayoub al-Sakhtiyani أيوب السختياني; Hameed bin Musa'da bin al-Mubarak حميد بن مسعدة بن المبارك (Sunan Abi Dawud)
Ibn ‘Umar reported the Apostle of Allaah(ﷺ) as saying “The month consists of twenty nine days, but do not fast till you sight it (the moon) and do not break your fast till you sight it. If the weather is cloudy, calculate it thirty days. When the twenty-ninth of Sha’ban came, Ibn ‘Umar would send someone (who tried) to sight the moon for him. If it was sighted then well and good, in case it was not sighted and there was no cloud and dust before him (on the horizon) he would not keep fa
Grade: Sahih

Hadith #2368 - Sunan Abi Dawud - Abu Qalaba, 'Abdullah bin Zayd al-Jarmi عبد الله بن زيد بن عمرو; Ahmed bin al-Miqdam أحمد بن المقدام; Ayoub al-Sakhtiyani أيوب السختياني; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي; Shadad bin Aus bin Thabit; Wahayb bin Khalid bin 'Ajlan al-Bahli وهيب بن خالد بن عجلان الباهلي (Sunan Abi Dawud)
The tradition mentioned above (No. 2361) has also been transmitted by Shaddad ibn Aws through a different chain of narrators. This version adds: While Shaddad ibn Aws was walking along with the Prophet (ﷺ)….The narrator then transmitted the rest of the tradition to the same effect.
Grade: Sahih

Hadith #2371 - Sunan Abi Dawud - Abdul Warith bin Sa'id bin Dhakwan عبد الوارث بن سعيد بن ذكوان; Abdullah bin 'Amr, Abu Ma'mar al-Mad'aq عبد الله بن عمرو - أبو معمر المقعد; Ayoub al-Sakhtiyani أيوب السختياني; ibn Abbas; Ikrama عكرمة (Sunan Abi Dawud)
The Prophet (ﷺ) as saying: A man who cups and a man who gets himself cupped break their fast. Abu Dawud said: Ibn Thawban transmitted a similar tradition from his father on the authority of Makhul through an chain of narrators mentioned by him.
Grade: Sahih

Hadith #2397 - Sunan Abi Dawud - Abu Hurairah; Ayoub al-Sakhtiyani أيوب السختياني; Habib al-Ma'lm Abu Muhammad حبيب المعلم أبو محمد البصري; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Hisham bin 'Urwa هشام بن عروة; Ibn Sirin محمد بن سيرين الأنصاري; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي (Sunan Abi Dawud)
Sufyan and Shu’bah differed among themselves on the name of the narrator Ibn al-Mutawwas and Abu al-Mutawwas.
Grade: Da'if

Hadith #2556 - Sunan Abi Dawud - Abdul Warith bin Sa'id bin Dhakwan عبد الوارث بن سعيد بن ذكوان; Ayoub al-Sakhtiyani أيوب السختياني; ibn Umar; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Nafie' نافع مولى ابن عمر (Sunan Abi Dawud)
Abu Hurairah reported the Apostle of Allaah(ﷺ) as saying “The bell is a wooden wind musical instrument of Satan.”
Grade: Sahih

Hadith #2557 - Sunan Abi Dawud - Abdullah bin al-Jahm عبد الله بن الجهم الرازي; Ahmed bin Abi Sarayj أحمد بن أبي سريج; Amr bin Abi Qays عمرو بن أبي قيس الرازي الأزرق كوفي; Ayoub al-Sakhtiyani أيوب السختياني; ibn Umar; Nafie' نافع مولى ابن عمر (Sunan Abi Dawud)
It has been prohibited to ride the beast which eats dung.
Grade: Sahih

Hadith #2560 - Sunan Abi Dawud - Abu Qalaba, 'Abdullah bin Zayd al-Jarmi عبد الله بن زيد بن عمرو; Ayoub al-Sakhtiyani أيوب السختياني; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Imran bin Husain; Sulaiman bin Harb سليمان بن حرب (Sunan Abi Dawud)
The Prophet (ﷺ) named our cavalry “the Cavalry of Allah,” when we were struck with panic, and when panic overtook us, the Messenger of Allah (ﷺ) commanded us to be united, to have patience and perseverance; and to be so when we fought.
Grade: Da'if

Hadith #2792 - Sunan Abi Dawud - Abu Qalaba, 'Abdullah bin Zayd al-Jarmi عبد الله بن زيد بن عمرو; Anas ibn Malik; Ayoub al-Sakhtiyani أيوب السختياني; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي; Wahayb bin Khalid bin 'Ajlan al-Bahli وهيب بن خالد بن عجلان الباهلي (Sunan Abi Dawud)
The Prophet (Saws) ordered a horned ram with black legs, black belly and black round the eyes, and it was brought from him to sacrifice. He said: ‘Aishah, get the knife then he said: Sharpen it with a stone. So I did. He took it, then take the ram he placed it on the ground and slaughtered it. He then said: In the name of Allah. O Allah, accept it for Muhammad, Muhammad’s family and Muhammad’s people. Then he sacrificed it.
Grade: Hasan

Hadith #2840 - Sunan Abi Dawud - Abdul Warith bin Sa'id bin Dhakwan عبد الوارث بن سعيد بن ذكوان; Abdullah bin 'Amr, Abu Ma'mar al-Mad'aq عبد الله بن عمرو - أبو معمر المقعد; Ayoub al-Sakhtiyani أيوب السختياني; ibn Abbas; Ikrama عكرمة (Sunan Abi Dawud)
To remove the injury is the shaving of the head.
Grade: Da'if

Hadith #2965 - Sunan Abi Dawud - al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Ayoub al-Sakhtiyani أيوب السختياني; Masdad bin Masrhad مسدد بن مسرهد بن مسربل (Sunan Abi Dawud)
The properties of Banu al-Nadir were part of what Allah bestowed on His Apostle from what the Muslims has not ridden on horses or camels to get; so they belonged specially to the Messenger of Allah (ﷺ) who gave his family their annual contribution. Ibn ‘Abdah said: His family (ahlihi) and not the members of his houses (ahl baitihi) ; then applied what remained for horses and weapons in Allah’s path.
Grade: Sahih

Hadith #3072 - Sunan Abi Dawud - Abdul Wahab bin 'Abdul Majeed al-Thaqaf عبد الوهاب بن عبد المجيد الثقفي; Ayoub al-Sakhtiyani أيوب السختياني; Hisham bin 'Urwa هشام بن عروة; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Sa'id bin Zayd; Urwa ibn al-Zubayr عروة بن الزبير (Sunan Abi Dawud)
The Prophet (ﷺ) gave az-Zubayr the land as a fief up to the reach of his horse when he runs. He, therefore, made his horse run until it stopped. He then threw his flog. Thereupon he said: Give him (the land) up to the point where his flog has reached.
Grade: Hasan

Hadith #3126 - Sunan Abi Dawud - Abdul Warith bin Sa'id bin Dhakwan عبد الوارث بن سعيد بن ذكوان; Ayoub al-Sakhtiyani أيوب السختياني; Hafsa bint Sirin حفصة بنت سيرين; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Umm Atiyyah Ansariyah (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) as saying: A child was born to me at night and I named him Ibrahim after his. He then narrated the rest of the tradition. Anas said: I saw it at the point of the death before the Messenger of Allah (ﷺ). Tears began to fall from the eyes of the Messenger of Allah (ﷺ). He said: The eye weeps and the heart grieves, but we say only what our Lord is pleased with, and we are grieved for you, Ibrahim.
Grade: Sahih

Hadith #3141 - Sunan Abi Dawud - Abdullah bin Muslima al-Qa'nabi عبد الله بن مسلمة بن قعنب القعنبي; Ayoub al-Sakhtiyani أيوب السختياني; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Ibn Sirin محمد بن سيرين الأنصاري; Imam Maalik مالك بن أنس بن مالك بن أبي عامر; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Umm Atiyyah Ansariyah (Sunan Abi Dawud)
By Allah, we did not know whether we should take off the clothes of the Messenger of Allah (ﷺ) as we took off the clothes of our dead, or wash him while his clothes were on him. When they (the people) differed among themselves, Allah cast slumber over them until every one of them had put his chin on his chest. Then a speaker spoke from a side of the house, and they did not know who he was: Wash the Prophet (ﷺ) while his clothes are on him. So they stood round the Prophet (ﷺ) and washed him
Grade: Hasan

Hadith #3142 - Sunan Abi Dawud - Ahmed bin 'Ubda bin Musa أحمد بن عبدة بن موسى; Ayoub al-Sakhtiyani أيوب السختياني; Ibn Sirin محمد بن سيرين الأنصاري; Umm Atiyyah Ansariyah; Yazid bin Zari' يزيد بن زريع (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) came in when his daughter died, and he said: Wash her with water and lotus leaves three or five times or more than that if you think fit, and put camphor, or some camphor in the last washing, then inform me when you finish. When we had finished we informed him, and he threw us his lower garment saying: Put it next to her body. Malik’s version has: that is, his lower garment (izar); and Musaddad did not say: He entered in.
Grade: Sahih

Hadith #3145 - Sunan Abi Dawud - Ayoub al-Sakhtiyani أيوب السختياني; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Ibn Sirin محمد بن سيرين الأنصاري; Muhammad bin 'Ubaid al-Tanafasi محمد بن عبيد بن أبي أمية الطنافسي (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) said to them while washing her daughter: Begin with her right side, and the places where the ablution is performed.
Grade: Sahih

Hadith #3166 - Sunan Abi Dawud - Ayoub al-Sakhtiyani أيوب السختياني; Hafsa bint Sirin حفصة بنت سيرين; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Sulaiman bin Harb سليمان بن حرب; Umm Atiyyah Ansariyah (Sunan Abi Dawud)
The Prophet (ﷺ) said: If any Muslim dies and three rows of Muslims pray over him, it will assure him (of Paradise). When Malik considered those who accompanied a bier to be a few, he divided them into three rows in accordance with this tradition.
Grade: Da'if

Hadith #3215 - Sunan Abi Dawud - Ayoub al-Sakhtiyani أيوب السختياني; Ibrahim bin Muhammad bin al-Harith إبراهيم بن محمد أبو اسحاق الفزاري; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
The Ansar came to the Messenger of Allah (ﷺ) on the day of Uhud and said: We have been afflicted with wound and fatigue. What do you command us? He said: Dig graves, make them wide, bury two or three in a single grave. He was asked: Which of them should be put first? He replied: The one who knew the Qur’an most. He (Hisham) said: My father Amir died on the day and was buried with two or one.
Grade: Sahih

Hadith #3238 - Sunan Abi Dawud - Abu Da'ud أبو داود السجستاني الأزدي; Amr bin Dinar عمرو بن دينار الأثرم الجمحي; Ayoub al-Sakhtiyani أيوب السختياني; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; ibn Abbas; Muhammad bin 'Ubaid al-Tanafasi محمد بن عبيد بن أبي أمية الطنافسي; Sa'id bin Jubayr سعيد بن جبير الأسدي; Sulaiman al-A'mash الأعمش / سليمان بن مهران; Sulaiman bin Harb سليمان بن حرب (Sunan Abi Dawud)
To the Messenger of Allah (ﷺ) was brought man wearing ihram who was thrown by his she-camel and has his neck broken and had died. He then said: Shroud him in his two garments, was him with water and lotus leaves, but do not cover his head, for he will be raised on the Day of Resurrection saying the talbiyah. Abu Dawud said: I heard Ahmad b. Hanbal say: There are five rules of the law (sunan) in this tradition: “Shroud him in his two garment,” that is, the dead should be shrouded in his two
Grade: Sahih

Hadith #3239 - Sunan Abi Dawud - Ayoub al-Sakhtiyani أيوب السختياني; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; ibn Abbas; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sa'id bin Jubayr سعيد بن جبير الأسدي (Sunan Abi Dawud)
“Shroud him in two garments.” Abu Dawud said: The narrator Sulaiman said the Ayyub said: “his two garments,” ‘Amr said: “tow garments,” Ibn ‘Ubaid said that Ayyub said: “in two garments” and Amr said: “in his two garments.” Sulaiman alone added: “do not put any perfume on him.”
Grade: Sahih

Hadith #3260 - Sunan Abi Dawud - Ahmad bin Hanbal أحمد بن حنبل; Ayoub al-Sakhtiyani أيوب السختياني; Nafie' نافع مولى ابن عمر; Sufyan bin 'Uyaynah سفيان بن عيينة (Sunan Abi Dawud)
A similar tradition has also been transmitted by Yusuf b. ‘Abd Allah b. Salam through a different chain of narrators.
Grade: Da'if

Hadith #3261 - Sunan Abi Dawud - Abdul Warith bin Sa'id bin Dhakwan عبد الوارث بن سعيد بن ذكوان; Ayoub al-Sakhtiyani أيوب السختياني; ibn Umar; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Muhammad bin 'Isa bin Hyan محمد بن عيسى بن حيان; Nafie' نافع مولى ابن عمر (Sunan Abi Dawud)
The Prophet (ﷺ) said: If anyone says when swearing an oath: “If Allah wills,” he makes an exception.
Grade: Sahih

Hadith #3299 - Sunan Abi Dawud - Ayoub al-Sakhtiyani أيوب السختياني; ibn Abbas; Ikrama عكرمة; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي; Wahayb bin Khalid bin 'Ajlan al-Bahli وهيب بن خالد بن عجلان الباهلي (Sunan Abi Dawud)
My sister took a vow to walk on foot to the House of Allah (i.e. Ka’bah). She asked me to consult the Prophet (ﷺ) about her. So I consulted the Prophet (ﷺ). He said: Let her walk and ride.
Grade: Sahih

Hadith #3315 - Sunan Abi Dawud - Abu Qalaba, 'Abdullah bin Zayd al-Jarmi عبد الله بن زيد بن عمرو; Ayoub al-Sakhtiyani أيوب السختياني; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Imran bin Husain; Muhammad bin 'Isa bin Hyan محمد بن عيسى بن حيان; Sulaiman bin Harb سليمان بن حرب (Sunan Abi Dawud)
(The Prophet asked): Does it contain an idol or was a festival of pre-Islamic times celebrated there ? He replied: No. I said: This mother of mine has taken a vow and walking (is binding on her). May I fulfill it on her behalf ? Sometimes the narrator Bashshar said: May we fulfill in on her behalf ? He said: Yes.
Grade: Sahih

Hadith #3367 - Sunan Abi Dawud - Abu Ja'far al-Nafaili عبد الله بن محمد أبو جعفر النفيلي الحران; Ayoub al-Sakhtiyani أيوب السختياني; ibn Umar; Nafie' نافع مولى ابن عمر (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) forbade the sale of fruits till they were clearly in good condition, forbidding it both to the seller and to the buyer.
Grade: Sahih

Hadith #3374 - Sunan Abi Dawud - Ayoub al-Sakhtiyani أيوب السختياني; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Jabir ibn 'Abdullah; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير; Sa'id bin Myna سعيد بن مينا (Sunan Abi Dawud)
The Prophet (ﷺ) forbade selling fruits years ahead, and commanded that unforeseen loss be remitted in respect of what is affected by blight. Abu Dawud said: The attribution of the tradition regarding the effect of blight is one-third of the produce to the Prophet (ﷺ) is not correct. This is the opinion of the people of Medina.
Grade: Sahih

Hadith #3395 - Sunan Abi Dawud - Ayoub al-Sakhtiyani أيوب السختياني; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Muhammad bin 'Ubaid al-Tanafasi محمد بن عبيد بن أبي أمية الطنافسي (Sunan Abi Dawud)
We used to employ people to till land for a share of it produce. He then maintained that, one of his uncles came to him and said: The Messenger of Allah (ﷺ) forbade us from a work which beneficial to us. But obedience to Allah and His Apostle (ﷺ) is more beneficial to us. We asked : What is that ? He said: The Messenger of Allah (ﷺ) said: If anyone has land, he should cultivate it, or lend it to his brother for cultivation. He should not rent it for a third or a quarter (of the produce) or
Grade: Sahih

Hadith #3403 - Sunan Abi Dawud - Ahmad bin Hanbal أحمد بن حنبل; Ayoub al-Sakhtiyani أيوب السختياني; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Jabir ibn 'Abdullah; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير; Sa'id bin Myna سعيد بن مينا (Sunan Abi Dawud)
The Prophet (ﷺ) said: If anyone sows in other people’s land without their permission, he has no right to any of the crop, but he may have what it cost him.
Grade: Sahih

Hadith #3436 - Sunan Abi Dawud - Abu Hurairah; al-Rabi' bin Nafi' Abu Tawba al-Halbi الربيع بن نافع أبو توبة الحلبي; Ayoub al-Sakhtiyani أيوب السختياني; Ibn Sirin محمد بن سيرين الأنصاري; Ubaidullah bin 'Amr bin Abi Walid عبيد الله بن عمرو بن أبي الوليد (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) as saying: None of you must buy in opposition to one another ; and do not go out to meet the merchandise, (but one must wait) till it is brought down to the market.
Grade: Sahih

Hadith #3443 - Sunan Abi Dawud - Abu Hurairah; Ayoub al-Sakhtiyani أيوب السختياني; Habib al-Ma'lm Abu Muhammad حبيب المعلم أبو محمد البصري; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Hisham bin 'Urwa هشام بن عروة; Ibn Sirin محمد بن سيرين الأنصاري; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) as saying: Do not go out to meet riders to conduct business with them ; none of you must buy in opposition to one another; and do not tie up the udders of camels and sheep, for he who buys them after that has been done has two courses open to him after milking them: he may keep them if he is pleased with them, or he may return them along with a sa’ of dates is he is displeased with them.
Grade: Sahih

Hadith #3454 - Sunan Abi Dawud - Ayoub al-Sakhtiyani أيوب السختياني; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; ibn Umar; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي; Nafie' نافع مولى ابن عمر (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) as saying: Each one of the two parties in a business has an option (to annul it) against the other party so long as they have not separated, except in a conditional bargain.
Grade: Sahih

Hadith #3503 - Sunan Abi Dawud - Abdullah bin 'Amr bin al-'Aas; Amr bin Shu'aib bin Muhammad عمرو بن شعيب بن محمد السهمي; Ayoub al-Sakhtiyani أيوب السختياني; Shu'aib bin Muhammad bin 'Abdullah شعيب بن محمد بن عبد الله بن عمرو; Zuhayr bin Harb زهير بن حرب بن شداد أبو خثيمة (Sunan Abi Dawud)
Hakim asked (the Prophet): Messenger of Allah, a man comes to me and wants me to sell him something which is not in my possession. Should I buy it for him from the market? He replied: Do not sell what you do not possess.
Grade: Sahih

Hadith #3602 - Sunan Abi Dawud - Abdullah bin 'Ubaidullah b. Abi Mulayka عبد الله بن عبيد الله بن أبي مليكة; Ayoub al-Sakhtiyani أيوب السختياني; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Sulaiman bin Harb سليمان بن حرب; Uqba binal-Harith bin 'Amir (Sunan Abi Dawud)
The Prophet (ﷺ) said: The testimony of a nomad Arab against a townsman is not allowable.
Grade: Sahih

Hadith #3603 - Sunan Abi Dawud - Abdullah bin 'Ubaidullah b. Abi Mulayka عبد الله بن عبيد الله بن أبي مليكة; Ahmed bin 'Abdullah أحمد بن عبد الله بن أبي; al-Harith bin 'Umayr Abu الحارث بن عمير أبو عمير; Ayoub al-Sakhtiyani أيوب السختياني; Uqba binal-Harith bin 'Amir; Uthman bin Muhammad (Sunan Abi Dawud)
“I married Umm Yahya daughter of Abu Ihab. A black woman entered upon us. She said that she had suckled both of us. So I came to the Prophet (ﷺ), and amentioned it to him. He turned away from me. I said (to him): Messenger of Allah! she is a liar. He said: What do you know? She has said what she has said. Separate yourself from her (wife).
Grade: Sahih

Hadith #3678 - Sunan Abi Dawud - Ayoub al-Sakhtiyani أيوب السختياني; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; ibn Umar; Muhammad bin 'Isa bin Hyan محمد بن عيسى بن حيان; Nafie' نافع مولى ابن عمر; Sulaiman bin Da'ud bin Da'ud سليمان بن داود بن داود بن علي (Sunan Abi Dawud)
Wine comes from these two trees, the date-palm and the grapes-vine. Abu Dawud said : The name of Abu KAthir al-Ubari is Yazid b. ‘Abd al-Rahman b. Ghufailat al-Sahmi. Some said: Uzainah. What is correct is Ghufailah.
Grade: Sahih

Hadith #3737 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; Ayoub al-Sakhtiyani أيوب السختياني; ibn Umar; Ma'mar bin Rashid معمر بن راشد; Nafie' نافع مولى ابن عمر (Sunan Abi Dawud)
If he is not fasting, he should eat, and if he is fasting, he should leave it.
Grade: Sahih

Hadith #3759 - Sunan Abi Dawud - Abdullah bin 'Ubaidullah b. Abi Mulayka عبد الله بن عبيد الله بن أبي مليكة; Ayoub al-Sakhtiyani أيوب السختياني; ibn Abbas; Masdad bin Masrhad مسدد بن مسرهد بن مسربل (Sunan Abi Dawud)
Abdullah ibn Ubaydullah ibn Umayr said: I was with my father in the time of Ibn az-Zubayr sitting beside Abdullah ibn Umar. Then Abbad ibn Abdullah ibn az-Zubayr said: We have heard that the evening meal is taken just before the night prayer. Thereupon Abdullah ibn Umar said: Woe to you! what was their evening meal? Do you think it was like the meal of your father?
Grade: Hasan

Hadith #3786 - Sunan Abi Dawud - Ahmed bin Abi Sarayj أحمد بن أبي سريج; Amr bin Abi Qays عمرو بن أبي قيس الرازي الأزرق كوفي; Ayoub al-Sakhtiyani أيوب السختياني; ibn Umar; Nafie' نافع مولى ابن عمر (Sunan Abi Dawud)
The Prophet (ﷺ) prohibited to drink the milk of the animal which feeds on filth.
Grade: Sahih

Hadith #3817 - Sunan Abi Dawud - al-Fadl bin Musa al-Synany الفضل بن موسى السيناني; al-Husain bin Waqid ak-Mervzi الحسين بن واقد المروزي; Ayoub al-Sakhtiyani أيوب السختياني; ibn Umar; Muhammad bin 'Abdul 'Aziz bin Abi Razma محمد بن عبد العزيز بن أبي رزمة; Nafie' نافع مولى ابن عمر (Sunan Abi Dawud)
Al-Faji’ came to the Messenger of Allah (ﷺ) and asked: Is not dead meat lawful for us? He said: What is your food? We said: Some food in the evening and some in the morning. AbuNu’aym said: Uqbah explained it to me saying: a cup (of milk) in the morning and a cup in the evening; this does not satisfy the hunger. So made the carrion lawful for them in this condition. Abu Dawud said: Ghabuq is a drink in the evening and Sabuh is a drink in the morning.
Grade: Da'if

Hadith #3940 - Sunan Abi Dawud - Ayoub al-Sakhtiyani أيوب السختياني; ibn Umar; Nafie' نافع مولى ابن عمر (Sunan Abi Dawud)
If anyone emancipates his share in slave, a fair price for the slave should be fixed, give his partners their shares, and the slave be thus emancipated. Otherwise he is emancipated to the extent of the share which he emancipated.
Grade: Sahih

Hadith #3941 - Sunan Abi Dawud - Ayoub al-Sakhtiyani أيوب السختياني; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; ibn Umar; Nafie' نافع مولى ابن عمر; Sulaiman bin Da'ud bin Da'ud سليمان بن داود بن داود بن علي (Sunan Abi Dawud)
He will be emancipated to the extent of the share which he emancipated, and sometimes he did not say these words.
Grade: Sahih

Hadith #3956 - Sunan Abi Dawud - Ahmad bin Hanbal أحمد بن حنبل; Ayoub al-Sakhtiyani أيوب السختياني; Jabir ibn 'Abdullah; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير (Sunan Abi Dawud)
The Prophet (ﷺ) said: You are more entitled to his price, and Allah has no need of it.
Grade: Sahih

Hadith #3957 - Sunan Abi Dawud - Abu Qalaba, 'Abdullah bin Zayd al-Jarmi عبد الله بن زيد بن عمرو; Ayoub al-Sakhtiyani أيوب السختياني; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Imran bin Husain; Sulaiman bin Harb سليمان بن حرب (Sunan Abi Dawud)
A man of the Ansar called Abu Madhkur declared that his slave called Ya’qub would be free after his death, but he had no other property. So the Messenger of Allah (ﷺ) called him and said: Who will buy him ? Nu’aim b. ‘Abd Allah b. al-Nahham bought him for eight hundred dirhams. When he handed them over to him, he (Prophet) said: If any of you is poor, he should begin from himself ; if anything is left over, give it to your family; if anything is left over, give it to your relatives ; if
Grade: Sahih

Hadith #3960 - Sunan Abi Dawud - Ayoub al-Sakhtiyani أيوب السختياني; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Ibn Sirin محمد بن سيرين الأنصاري; Imran bin Husain; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Yahya bin Atyq al-Tfawy يحيى بن عتيق الطفاوي (Sunan Abi Dawud)
A man of the Ansar … The Prophet (ﷺ) said: Had I been present before his burial, he would not have been buried in a Muslim cemetry.
Grade: Sahih

Hadith #4193 - Sunan Abi Dawud - Ayoub al-Sakhtiyani أيوب السختياني; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; ibn Umar; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي; Nafie' نافع مولى ابن عمر (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) forbade qaza’. Qaza’ means having part of a boy’s head shaved and leaving part unshaven.
Grade: Sahih

Hadith #4194 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Ahmad bin Hanbal أحمد بن حنبل; Ayoub al-Sakhtiyani أيوب السختياني; ibn Umar; Ma'mar bin Rashid معمر بن راشد; Nafie' نافع مولى ابن عمر (Sunan Abi Dawud)
the Prophet (ﷺ) forbade qaza’ which means that the head of a boy is shaved and a lock is left.
Grade: Sahih

Hadith #4251 - Sunan Abi Dawud - Abu Qalaba, 'Abdullah bin Zayd al-Jarmi عبد الله بن زيد بن عمرو; Ayoub al-Sakhtiyani أيوب السختياني; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Muhammad bin 'Isa bin Hyan محمد بن عيسى بن حيان; Sulaiman bin Harb سليمان بن حرب; Thawban bin Bujdud (Sunan Abi Dawud)
Salah is near Khaibar.
Grade: Sahih

Hadith #4267 - Sunan Abi Dawud - al-Ahnaf bin Qays الأحنف بن قيس بن معاوية; al-Hasan al-Basri الحسن البصري; Ayoub al-Sakhtiyani أيوب السختياني; Fdyl bin Husayn bin Talha فضيل بن حسين بن طلحة; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Yonus bin Yazid bin Abi al-Nijad يونس بن يزيد بن أبي النجاد (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) as saying: A Muslim’s best property will soon be sheep which he will take to the tops of the mountains and the places where the rain falls, fleeing with his religion from the civil strife (fitan).
Grade: Sahih

Hadith #4268 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Ayoub al-Sakhtiyani أيوب السختياني; Ma'mar bin Rashid معمر بن راشد; Muhammad bin Abi Sari محمد بن أبي السري (Sunan Abi Dawud)
I came out with the intention of (participating in) fighting. Abu Bakrah met me and said: Go back, for I heard the Messenger of Allah (ﷺ) say: When two Muslims face each other with their swords, the killer and the slain will go to Hell. He asked: Messenger of Allah, this is the killer (so naturally he should go to Hell), but what is the matter with the slain ? He replied: He intended to kill his companion.
Grade: Sahih

Hadith #4349 - Sunan Abi Dawud - Ahmad bin Hanbal أحمد بن حنبل; Ayoub al-Sakhtiyani أيوب السختياني; Ikrama عكرمة (Sunan Abi Dawud)
The Prophet (ﷺ) said: Allah will not fail to detain this community for less than half a day.
Grade: Sahih

Hadith #4362 - Sunan Abi Dawud - Abu Qalaba, 'Abdullah bin Zayd al-Jarmi عبد الله بن زيد بن عمرو; Anas ibn Malik; Ayoub al-Sakhtiyani أيوب السختياني; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Sulaiman bin Harb سليمان بن حرب (Sunan Abi Dawud)
A Jewess used to abuse the Prophet (ﷺ) and disparage him. A man strangled her till she died. The Messenger of Allah (ﷺ) declared that no recompense was payable for her blood.
Grade: Da'if

Hadith #4393 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Ayoub al-Sakhtiyani أيوب السختياني; Hassan ibn Ali bin Abi Talib; ibn Umar; Ma'mar bin Rashid معمر بن راشد; Mkhld bin Khalid bin Yazid مخلد بن خالد بن يزيد الشعيري; Mkhld bin Yazid al-Quraishi مخلد بن يزيد القرشي الحراني; Nafie' نافع مولى ابن عمر (Sunan Abi Dawud)
Cutting of the hand is not be inflicted on one who snatches something. Abu Dawud said : Ibn Juraij did not hear these two traditions from Abu al-Zubair, I have been informed by Ahmad. B. Hanbal saving : Ibn Juraij heard them from Yasin al-Zayyat. Aby Dawud said: Al-Mughirah b. Muslim has transmitted it from Abu al-Zubair from Jabir From the prophet(ﷺ).
Grade: Sahih

Hadith #4526 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Abu Qalaba, 'Abdullah bin Zayd al-Jarmi عبد الله بن زيد بن عمرو; Ahmed bin Salah al-Masri أحمد بن صالح المصري; Anas ibn Malik; Ayoub al-Sakhtiyani أيوب السختياني; Ma'mar bin Rashid معمر بن راشد (Sunan Abi Dawud)
On the authority of some men of the Ansar : The Prophet (ﷺ) said to the Jews and started with them: Fifty of you should take the oaths. But they refused (to take the oaths). He then said to the Ansar: Prove your claim. They said: Do we take the oaths without seeing, Messenger of Allah? The Messenger of Allah (ﷺ) then imposed the blood-wit on the Jews because he (the slain) was found among them.
Grade: Da'if

Hadith #4580 - Sunan Abi Dawud - Ayoub al-Sakhtiyani أيوب السختياني; Hammad bin Salama حماد بن سلمة; ibn Abbas; Ikrama عكرمة; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي (Sunan Abi Dawud)
The price of a male or a female slave is five hundred dirhams. Abu Dawud said: Rabi’ah said: The price of a male or a female slave is fifty dinars.
Grade: Da'if

Hadith #4620 - Sunan Abi Dawud - Ayoub al-Sakhtiyani أيوب السختياني; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Sulaiman bin Harb سليمان بن حرب (Sunan Abi Dawud)
Between them and their faith.
Grade: Da'if

Hadith #4623 - Sunan Abi Dawud - Ayoub al-Sakhtiyani أيوب السختياني; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Sulaiman bin Harb سليمان بن حرب (Sunan Abi Dawud)
Qurrah b. Khalid used to tell us: O young people! Do not think that al-Hasan denied predestination, for his opinion (i.e., belief) was sunnah and sight.
Grade: Sahih

Hadith #4743 - Sunan Abi Dawud - Ayoub al-Sakhtiyani أيوب السختياني; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; ibn Umar; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Nafie' نافع مولى ابن عمر; Sulaiman bin Harb سليمان بن حرب (Sunan Abi Dawud)
Every son of Adam will be devoured by the earth with the exception of the tail-bone from which he was created and from which he will be reconstituted.
Grade: Sahih

Hadith #4761 - Sunan Abi Dawud - Ali ibn Abi Talib; Ayoub al-Sakhtiyani أيوب السختياني; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Ibn Sirin محمد بن سيرين الأنصاري; Muhammad bin 'Isa bin Hyan محمد بن عيسى بن حيان; Muhammad bin 'Ubaid al-Tanafasi محمد بن عبيد بن أبي أمية الطنافسي (Sunan Abi Dawud)
He who disapproves is guiltless, and he who disapproves is safe. Qatadah said : it means one who feels its disapproval in his heart, and one who expresses disapproval in his heart.
Grade: Sahih

Hadith #4963 - Sunan Abi Dawud - Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Abu Hurairah; Ayoub al-Sakhtiyani أيوب السختياني; Ibn Sirin محمد بن سيرين الأنصاري; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sufyan bin 'Uyaynah سفيان بن عيينة (Sunan Abi Dawud)
Zayd ibn Aslam quoted his father as saying: Umar ibn al-Khattab (Allah be pleased with him) struck one of his sons who was given the kunyah AbuIsa, and al-Mughirah ibn Shu’bah had the kunyah AbuIsa. Umar said to him: Is it not sufficient for you that you are called by the kunyah AbuAbdullah? He replied: The Messenger of Allah (ﷺ) gave me this kunyah. Thereupon he said: The Messenger of Allah (ﷺ) was forgiven all his sins, past and those followed. But we are among the people similar to us.
Grade: Hasan Sahih

Hadith #4973 - Sunan Abi Dawud - Abu Hurairah; Ayoub al-Sakhtiyani أيوب السختياني; Habib bin al-Shaheed al-Azdi حبيب بن الشهيد الأزدي; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Hisham bin 'Urwa هشام بن عروة; Ibn Sirin محمد بن سيرين الأنصاري; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي (Sunan Abi Dawud)
To proceed (amma ba’d)
Grade: Sahih

Hadith #5017 - Sunan Abi Dawud - Abdul Wahab bin 'Abdul Majeed al-Thaqaf عبد الوهاب بن عبد المجيد الثقفي; Abu Hurairah; Ayoub al-Sakhtiyani أيوب السختياني; Muhammad bin Ja'far Ghandar محمد بن جعفر غندر صاحب الكرابيس; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل (Sunan Abi Dawud)
When the Messenger of Allah (ﷺ) finished the dawn prayer, he would ask: Did any of you have a dream last night? And he said: All that is left of Prophecy after me is a good vision.
Grade: Sahih

Hadith #5022 - Sunan Abi Dawud - Ayoub al-Sakhtiyani أيوب السختياني; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; ibn Abbas; Ikrama عكرمة; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sulaiman bin Da'ud bin Da'ud سليمان بن داود بن داود بن علي (Sunan Abi Dawud)
When one of you sees a vision which he dislikes, he must spit on his left (three times), seek refuge in Allah from the devil three times, and turn from the side on which he was lying.
Grade: Sahih

Hadith #5252 - Sunan Abi Dawud - Ayoub al-Sakhtiyani أيوب السختياني; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; ibn Umar; Muhammad bin 'Ubaid al-Tanafasi محمد بن عبيد بن أبي أمية الطنافسي; Nafie' نافع مولى ابن عمر (Sunan Abi Dawud)
Kill snakes, kill those which have two streaks and those with small tails, for they obliterate the eyesight and cause miscarriage. Salim said: ‘Abd Allah(b. ‘Umar) used to kill every snake which he found. Abu Lubabah or Zaid b. al-Khattab saw him chasing a snake. He said: He(the Prophet) prohibited house-snakes.
Grade: Sahih